2019
DOI: 10.1111/jep.13168
|View full text |Cite
|
Sign up to set email alerts
|

Assessing whether cancer stage is needed to evaluate measures of hospital surgical performance

Abstract: Rational, aims, and objectives: While public reports of hospital-level surgical quality measures are becoming increasingly common in health care, a comprehensive national assessment of surgical quality across multiple cancer sites has yet to be developed.Fee-for-service (FFS) Medicare claims present a potential resource from which to measure outcomes following cancer surgery given the national scope of patients and providers.However, due to the administrative nature of the data, clinical cancer information suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The advantage of the FFS Medicare claims dataset is that it comprehensively covers the entire United States. A shortcoming is that it does not have the type of detailed information about cancer site that cancer registries contain, but prior analyses demonstrate that risk‐adjusted surgical outcome assessment is robust to the exclusion of these SEER variables . While we relied on the Charlson comorbidity index for our risk adjustment, which is a widely accepted method in the field, all risk adjustment can be criticized for being incomplete .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of the FFS Medicare claims dataset is that it comprehensively covers the entire United States. A shortcoming is that it does not have the type of detailed information about cancer site that cancer registries contain, but prior analyses demonstrate that risk‐adjusted surgical outcome assessment is robust to the exclusion of these SEER variables . While we relied on the Charlson comorbidity index for our risk adjustment, which is a widely accepted method in the field, all risk adjustment can be criticized for being incomplete .…”
Section: Discussionmentioning
confidence: 99%
“…Although FFS Medicare claims do not include clinical information regarding cancer stage, we previously demonstrated that risk adjustment was not sensitive to the inclusion or absence of this information. 31 Hospital characteristics came from the AHA database including hospitals' location (rural/urban), organizational control (not-for-profit, private, government), and teaching status (defined as a member of the council of teaching hospitals of the American Medical Association). 28 These characteristics were not available for 84 hospitals (2.2% of the sample) and were excluded from analyses that depended on these characteristics.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated with chemotherapy, radiotherapy, or surgery at an acute care or critical access hospital in 2006, 2011, 2012, and 2013 (index years) were in the analysis and we obtained 4-year mortality ratios for each hospital in 2010, 2015, 2016, and 2017 respectively (data available from our previous studies (3)(4)(5). Hospitals were identified across index years via the Centers for Medicare and Medicaid Services Certification Numbers.…”
Section: Study Samplementioning
confidence: 99%
“…Hospitals were then divided into quartiles based on their total FFS Medicare patient volume combined across index years. As per prior work, Medicare FFS beneficiaries were included if they initiated cancer treatment or management of recurrent disease in the index year indicated by an absence of claims for cancer in the previous year (3)(4)(5)(6).…”
Section: Study Samplementioning
confidence: 99%